Character Values In Pemayuh Oton Sungsang Carik Ceremony In Pengiangan Kawan - I Dewa Made Weda Mudita; I Nengan Duija; Ni Komang Sutriyanti (Jayapangus Press, 2019)
Pemayuh oton sungsang carik ceremony is very rare, carried out because it was not socialized, either in the form of books or socialization directly. Pemayuh oton sungsang carik ceremony is carried out by the people who have a birth and have special characteristics or abnormalities. When metenung used Lontar Wrhaspatikalpa which owned by Dewa Aji Mangku Pradah Pengiangan Kawan village. In the ejection, it was explained that those who had a birth on a certain day and certain time were called breech, which resulted in the death of starch (salah pati), causing starch (ulah pati) or unnatural death. Based on the data analysis found that (1) the cause of pemayuh oton sungsang carik is to arise because the faith of the people towards the influence of the day of birth, and the irregularities of one's behavior attract the attention of parents or family members in the household. In order to know about the causes of anomalies or the peculiarities of their children's behavior, they will be assigned to the day of birth or oton. Based on the results, pemayuh oton sungsang carik ceremony was carried out. (2) The implementation is based on literary sources in the form of ejection, Lontar Wrehaspati Kalpa, Lontar Tenung Pawetuan and Lontar Sang Hyang Aji Nyug. Based on structural functional theory, there are four important functions. The functions such as: (A) Adaptation function, (G) Functioning Goal Attainment, (I) Functions of integration, and (L) Functioning Latency. (3) Character Values ​contained in Pemayuh Oton Sungsang Carik Ceremony form 18 character values.